2015
DOI: 10.1021/acs.est.5b03593
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Honeybee Colony Failure: Using the BEEHAVE Model to Simulate Colony Responses to Pesticides

Abstract: To simulate effects of pesticides on different honeybee (Apis mellifera L.) life stages, we used the BEEHAVE model to explore how increased mortalities of larvae, in-hive workers, and foragers, as well as reduced egg-laying rate, could impact colony dynamics over multiple years. Stresses were applied for 30 days, both as multiples of the modeled control mortality and as set percentage daily mortalities to assess the sensitivity of the modeled colony both to small fluctuations in mortality and periods of low to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
55
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 44 publications
(57 citation statements)
references
References 40 publications
2
55
0
Order By: Relevance
“…infectious agents, climatic and habitat changes, resources, etc.) Feedback mechanisms in honeybee colonies make it challenging to extrapolate effects measured at the individual level mostly under laboratory conditions to potential adverse effects on colony processes and population dynamics observed under field conditions (Rumkee et al, 2015). There is still a lack of good knowledge of the potential interactions and effects of these multiple stressors at the colony level and in field conditions.…”
Section: Moving Towards Integrated Eras To Account For Multiple Stresmentioning
confidence: 99%
See 2 more Smart Citations
“…infectious agents, climatic and habitat changes, resources, etc.) Feedback mechanisms in honeybee colonies make it challenging to extrapolate effects measured at the individual level mostly under laboratory conditions to potential adverse effects on colony processes and population dynamics observed under field conditions (Rumkee et al, 2015). There is still a lack of good knowledge of the potential interactions and effects of these multiple stressors at the colony level and in field conditions.…”
Section: Moving Towards Integrated Eras To Account For Multiple Stresmentioning
confidence: 99%
“…stressors, some of which contributed to honeybee colony losses in many parts of the world (van Engelsdorp and Meixner, 2010;Potts et al, 2010;Laurent et al, 2015). In addition, determining the colony level impact of an individual effect is difficult because stressors can affect individuals in a number of ways (Rumkee et al, 2015). It is therefore difficult to predict how the stressors change colony dynamics separately and in combination (Thompson, 2012;ANSES, 2015).…”
Section: Moving Towards Integrated Eras To Account For Multiple Stresmentioning
confidence: 99%
See 1 more Smart Citation
“…Rumkee et al [31] used BEEHAVE to simulate effects on queen egg-laying rate and mortality of different life stages and found that the colony was most sensitive to loss of workers, so in the present study we focus on sublethal effects on workers. Rumkee et al [31] used BEEHAVE to simulate effects on queen egg-laying rate and mortality of different life stages and found that the colony was most sensitive to loss of workers, so in the present study we focus on sublethal effects on workers.…”
Section: Introductionmentioning
confidence: 99%
“…10 To understand the role that each of the factors pesticides, parasites and lack of floral resources, 11 may play in honeybee colony failure, multi-stress models are needed that deal with hive 12 dynamics, parasitic infections as well as contaminants . The BEEHAVE 13 model is an example of such a model ; Rumkee et al 2015) that can be 14 exploited to disentangle the multi-stress interactions. nearby, most foraging will take place within a few kilometres.…”
mentioning
confidence: 99%